Insecticide use on vegetables in Ghana: Would GM seed benefit farmers? - Horna, Daniela; Smale, Melinda; Al-Hassan, Ramatu M.; Falck-Zepeda, José B.; Timpo, Samuel E. (International Food Policy Research Institute, 2008)
Tomato, cabbage, and garden egg (African eggplant, or Solanum aethiopicum) are important crops for small-scale farmers and migrants in the rural and peri-urban areas of Ghana. Genetic modification has the potential to alleviate poverty through combating yield losses from pests and diseases in these crops, while reducing health risks from application of hazardous chemicals. This ex ante study uses farm survey data to gauge the potential for adoption of genetically modified (GM) varieties, estimate the potential impact of adoption on farm profits, and highlight economic differences among the three crops. Farmers' expenditures on insecticides are below the economic optimum in all three crops, and the estimated function for damage abatement shows that insecticide amounts are significant determinants of cabbage yields only. Nonetheless, yield losses from pests and disease affect insecticide use. A stochastic budget analysis also indicates a higher rate of return to vegetable production with the use of resistant seeds relative to the status quo, even considering the technology transfer fee for GM seed. Non-insecticide users could accrue higher marginal benefits than current insecticide users. Comparing among vegetable crops with distinct economic characteristics provides a wider perspective on the potential impact of GM technology. Until now, GM eggplant is the only vegetable crop that has been analyzed in the peer-reviewed, applied economics literature. This is the first analysis that includes African eggplant.